Engine exhaust manifold with thermoelectric generator unit. (July 2021) - Royale, Andrew; Simic, Milan; Lappas, Petros
Thermal energy recovery systems are subject of intensive research activities in automotive engineering. They are becoming appealing because of the energy savings, low maintenance requirements and compact designs. Another element is the increase in working temperature ranges over the previous maximum of 400 °C. This was limiting the positioning of these devices to mid and rear locations of the exhaust systems. They also contained a specially designed cooling system for the cold side of the thermoelectric generator unit, which effectively preformed the requirements of the cold junction point (Seebeck effect) between the "P" and "N" semiconductors. Currently, thermoelectric generator manufacturers are producing devices that could operate at the temperatures over 850 °C which is opening up different research and application opportunities. This research report shows a continuation of previous research work carried out, to test 850 °C thermoelectric generator units, using the performance specifications and measurements conducted in our labs. We have extrapolated and predicted power output further. In the research, we covered the concept of placing high-temperature thermoelectric generator units directly into the exhaust port of the engine, just outside the cylinder head. Novel development solution is presented, where a new thermoelectric generator unit is designed to be adaptable to the profile of the exhaust port. Computational fluid dynamics analysis was conducted on a real-world engine and concept models, confirming consistent thermal heat transfer from the combustion chamber of the engine into the exhaust manifold thermoelectric generator unit assembly. Cooling of the device is achieved by direct coolant flow from the cylinder head. It could also be realized using an external cooling system.